Impact of IFRS 8 on segment reporting usefulness in the largest European companies - Jan Michalak (Zeszyty Teoretyczne Rachunkowości)
The aim of the paper is to analyse the impact of change in accounting regulations – the replacement of IAS 14 by IFRS 8 – on the form and content of segment reporting of the largest companies from Poland and other European countries and on its usefulness for users. In order to achieve the objective of the article, literature study and comparative empirical research were conducted. The empirical study covered 355 entities from 15 countries. Data for fourteen countries were taken from research carried out by Nich-ols et al. (2012), and data for Polish firms were collected by the author. Conclusions of the study indicate neutral, positive and negative effects of the introduction of IFRS 8 on financial statements usefulness. In most cases was observed a lack of clear impact of the implementation of IFRS 8 on segment reports content and usefulness. Neutral consequences of the enforcement of the new standard for financial report-ing are particularly evident in two respects. Firstly, most of the companies did not change the number or criteria of segment disclosure. Secondly, reduction in the scope of disclosure on geographical segments, envisaged by some IFRS 8 critics, did not materialize. Positive changes resulting from IFRS implementa-tion include: reduction in the number of single segment entities, significant increase in the number of segments and possibility to see an entity through the eyes of management. The negative effect of the accounting regulation change is the reduction in the scope of disclosures – especially on segment liabili-ties and segment capital expenditure